2023
DOI: 10.1007/s10895-022-03140-9
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Probe Based on the Hydrazone Schiff Base for the Detection of Zn2+ and its Application on Test Strips

Abstract: A novel uorescent probe SHK for Zn 2+ detection was designed based on the hydrazone Schiff base, successfully synthesized by Suzuki coupling and condensation reactions. The probe SHK in DMSO/H 2 O showed extremely weak uorescence. However, the solution exhibited an intensive yellow-green emission with the introduction of Zn 2+ . In contrast, negligible uorescence change was observed when other metal ions were added, suggesting a high selectivity of SHK for Zn 2+ detection. The Job's Plot analysis revealed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The corresponding plot of fluorescence intensity versus Zn 2+ concentration was constructed, and a strong linear correlation (Y=‐81.23867+1.0517E8*X, R 2 =0.99591, Figure 3b) was observed over the range of 1~10 μM. Importantly, the remarkable limit of detection (LOD) for Zn 2+ using the rule of 3σ/slope, [40–42] was calculated to be 1.04×10 −7 M compared to the previously published probes [6,26,27,43–59] (Table 1). In addition, the association constant ( K ) for L− Zn 2+ complexation was determined by Benesi‐Hildebrand equation: Fmax-FminF-Fmin=1K[]M+1 ${{{{F}_{max}-{F}_{min}}\over{F-{F}_{min}}}={{1}\over{K\left[M\right]}}+1}$ , [60] to be 3.496×10 4 M −1 (Figure S10), which confirms binding affinity of L towards Zn 2+ .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The corresponding plot of fluorescence intensity versus Zn 2+ concentration was constructed, and a strong linear correlation (Y=‐81.23867+1.0517E8*X, R 2 =0.99591, Figure 3b) was observed over the range of 1~10 μM. Importantly, the remarkable limit of detection (LOD) for Zn 2+ using the rule of 3σ/slope, [40–42] was calculated to be 1.04×10 −7 M compared to the previously published probes [6,26,27,43–59] (Table 1). In addition, the association constant ( K ) for L− Zn 2+ complexation was determined by Benesi‐Hildebrand equation: Fmax-FminF-Fmin=1K[]M+1 ${{{{F}_{max}-{F}_{min}}\over{F-{F}_{min}}}={{1}\over{K\left[M\right]}}+1}$ , [60] to be 3.496×10 4 M −1 (Figure S10), which confirms binding affinity of L towards Zn 2+ .…”
Section: Resultsmentioning
confidence: 80%
“…Then the immersed test strips were treated with different metal ion solutions (1 mmol/L) for 30 min, and the changes were observed under the 365 nm ultraviolet lamp. As we can see from Figure 8, only the test strip treated with Zn 2+ ions exhibited yellow fluorescence, indicating that such test strips have potential applications in the qualitative detection of Zn 2+ ions [58,59] …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For the determination of Zn 2+ ions, a fluorescent Schiff base sensor 1 (Figure 1) was synthesized by Gau Xu and his research group. 47 Xu et al reported a hydrazone Schiff base based chemosensor that was further characterized by various spectroscopic techniques. The sensor showed weak fluorescence alone, but with the incorporation of Zn 2+ ions, the intensity of fluorescence enhanced rapidly and exhibited an intense yellow-green emission.…”
Section: Schiff Base Probes For Zn 2+ Recognitionmentioning
confidence: 99%
“…[ 25–27 ] The fundamentals of fluorescent detection are based on the interaction between probes and metal ions, through the change in the color, ultraviolet absorption, fluorescence, and other physical/chemical properties, to achieve the selective recognition of metal ions. [ 28–30 ] It should be noted that two facts cannot be ignored in the fluorescence detection of Zn 2+ ions. First, it is relatively difficult to detect Zn 2+ ions due to a fully colorless complex of Zn 2+ in an aqueous solution and filled 3d 10 orbit.…”
Section: Introductionmentioning
confidence: 99%